The Archive: Digital Art and an Unsustainable Future - Tallulah Harvey (Janeway JS, 2018)
This short story, “The Archive”, grew out of the eco-critical research I underwent during my postgraduate degree at Goldsmiths, University of London. In recent years, literary studies have become increasingly invested in environmentalism. The damaging consequences of human endeavour are now widely regarded within environmentalist and scientific communities, and by environmental literary theory or “ecocriticism”, as a shift from the Holocene (the geological epoch that provided the appropriate conditions for mammals to thrive), to the “Anthropocene” (the epoch in which human activity has become the dominant driving force of climatic change). The ecological implications of the Anthropocene prompt questions regarding human enterprise and responsibility; fuelling dystopian or apocalyptic end of the world narratives and anxieties towards technology, capitalism and post-humanism. This short piece explores the current problems facing climate change activists, namely the inconsistencies between the scientific community’s attitude towards ecological degradation and popular culture’s. Slajov Zizek suggests that public denial and the disassociation from environmental disaster is not caused by a lack of scientific knowledge, but because we as individuals fail to corroborate what we already know about climate change with our sensory experience of the everyday: ‘We know it, but we cannot make ourselves believe in what we know’. The Archive questions this pervasive delusion, one that denies climate change even in the face of dwindling resources, increasing natural disaster and rising sea levels. We as a society consume natural resources excessively, without any regard for the consequences. My work draws attention to the suicidal nature of this desire, and encourages its readers to take responsibility for their actions, for the sake of humanity’s survival.